Low-cost media for Bt-based biopesticides mass production and their efficacy against Spodoptera frugiperda - ACHMAD DJUNAEDY; ADINDA ROHMA JULIVIA; APRILIAWATI APRILIAWATI; GITA PAWANA; DITA MEGASARI; SYAIFUL KHOIRI (Smujo International, 2026)
Abstract. Djunaedy A, Julivia AR, Apriliawati, Pawana G, Megasari D, Khoiri S. 2026. Low-cost media for Bt-based biopesticides mass production and their efficacy against Spodoptera frugiperda. Asian J Agric 10 (1): g100164. https://doi.org/10.13057/asianjagric/g100164. Fall armyworm, Spodoptera frugiperda, is a destructive pest that threatens maize production worldwide. Biopesticides derived from Bacillus thuringiensis (Bt) offer a sustainable alternative to chemical insecticides; however, their widespread adoption is often constrained by the high cost of production media. This study aimed to develop low-cost media using locally available flours (tapioca, arrowroot, mung bean, and soybean) for Bt-based biopesticide production and to evaluate their efficacy against S. frugiperda larvae. Bacillus thuringiensis strain Bt21was inoculated into each low-cost medium, and their bacterial growth was recorded. Bacterial viability during eight weeks of storage was monitored weekly using the spread agar methods. Insecticidal activity was evaluated through larval bioassays using ten larvae per experimental unit with four replications. Larval mortality was recorded and determined using probit analysis to estimate Lethal Concentration (LC) and Lethal Time (LT) values. The results showed that among the four flour, tapioca-based medium supported the highest bacterial growth and maintained viability over time compared with others. At 15% concentration, Bt formulations using tapioca and arrowroot resulted in the highest larval mortality (95% and 90%, respectively), with low LC₅₀ values (1.67% and 1.80%) and rapid LT₅₀ value (3.20 h and 9.07 h). In contrast, mung bean and soybean-based media were found less effective, exhibiting higher LC and LT values. These findings demonstrate that substrate composition significantly influences bacterial viability and insecticidal activity. In conclusion, tapioca and arrowroot flours are effective and low-cost substrates for Bt-based biopesticide production and offer promising options for sustainable pest management. The use of locally available agricultural resources can support more economical and environmentally friendly biopesticide development for farming systems.